Outcomes of a homestead food production program on nutritional knowledge, dietary diversity, food security and empowerment of rural women in Tehran province, Iran - Neda Ezzeddin; Naser Kalantari; Morteza Abdollahi; Parisa Amiri; Bahareh Amini; Farid Zayeri (BMC Public Health, 2024)
Abstract Background Food and nutrition insecurity is a major health issue in developing countries. Homestead food production (HFP) programs are strategies for improving food and nutrition security of a country. Iran implemented a HFP program entitled “Nutrition Improvement of Rural and Nomadic Women” in its villages for a five-year period from 2017. The current study assessed the outcomes of this mentioned program and its determinants among rural women in Tehran province. Methods The population of this cross-sectional study comprised a group covered by the program (n = 143) and a non-covered group (n = 160). The participants were selected randomly from 32 villages of five counties in Tehran province. Data was collected using five questionnaires: (1) General information, (2) Women’s empowerment, (3) Nutritional knowledge, (4) Dietary diversity, and (5) Household Food Insecurity Access Scale (HFIAS). Data was analyzed using the IBM SPSS version 21 and the IBM Amos SPSS version 22 software. Results The results of the study showed no significant improvement in the expected indicators, such as frequency of home gardening, nutritional knowledge, dietary diversity, women’s empowerment, and household food insecurity status among women covered by the program (p > 0.05). The structural equation modelling (SEM) results indicated that women’s empowerment from the dimension of decision-making power (r = 0.151) and nutritional knowledge (r = 0.135) were the significant positive predictors of dietary diversity (p < 0.05), while household food insecurity predicted it negatively (r=-0.138) (p < 0.05). Conclusion Because the current evaluated program has not been able to improve the expected indicators, modification of the program implementation may be needed, such as: addressing the probable barriers and challenges and strengthening the facilities in the covered villages. The current study presents a model of the dietary diversity predictors for consideration in redesigning or enhancing the program.